Book review: Radha R. Sharma (Ed.), Human Resource Management for Organizational Sustainability. Issue 1 (March 2020) - Sharma, Subhash
Radha R. Sharma (Ed.), Human Resource Management for Organizational Sustainability, New York: Business Expert Press, 2019, 211 pp., 36.95 (Print), 19.95 (Ebook). ISBN: 9781947098022.